2016
DOI: 10.1186/s12902-016-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Results of a prospective multicenter neuroendocrine tumor registry reporting on clinicopathologic characteristics of Greek patients

Abstract: BackgroundThe rare incidence of neuroendocrine neoplasms (NENs) has contributed to a paucity of large epidemiologic studies of patients with this condition. We investigated the occurrence and clinicopathologic features of NENs in Greece.MethodsBetween October 2010 and November 2012 we collected data on 246 newly diagnosed patients from a broad-based multi-institutional registry that comprises eight academic and hospital sites in Greece. The WHO 2010 pathologic classification and the 7th AJCC Staging system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…The median age of the patients at our study was 55.7 years, similar to other studies (Niederle et al, 2010;Araujo et al, 2013;Lewkowicz et al, 2015;Nikou et al, 2016). Five percent of the cases were asymptomatic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The median age of the patients at our study was 55.7 years, similar to other studies (Niederle et al, 2010;Araujo et al, 2013;Lewkowicz et al, 2015;Nikou et al, 2016). Five percent of the cases were asymptomatic.…”
Section: Discussionsupporting
confidence: 89%
“…Grade and Ki-67 ratio are required for pathologic classification and have prognostic significance. The Ki67 ratio was found to be <2% in most of the studies (Garcia-Carbonero et al, 2010;Niederle et al, 2010;Lim et al, 2011;Araujo et al, 2013;Lewkowicz et al, 2015;Nikou et al, 2016;Lim et al, 2017). Likewise, in our study, the Ki67 rate was found to be ≤2% in 63.1%, 3-20% in 7.1%, and >20% in 25% of patients.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results provide a comprehensive and relevant information on a group of neoplasm still poorly characterized, particularly, in Southern Europe. Published data from GEP-NEN in European countries is available in a French registration study [7], in a Spanish study of the Neuroendocrine Tumours Study Group Registry of Spain (RGETNE) [8], in an Italian epidemiological study [9], in a prospective Greek registry [10], and in the United Kingdom and Northern European countries [1113]. Worldwide, the most characterized cohorts are from the United States of America (USA) [2, 14], and there is data available from Asian countries, such as China [15] and Japan [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their identification over a century ago, the natural history of NENs remains inadequately understood. Their rarity, heterogeneity, and unique phenotypic, hormonally driven variation, expressed by nonspecific but debilitating symptoms, hamper efforts to totally understand their biological characteristics [2,[4][5][6]. However, according to the largest and most recent population-based study of NENs conducted in the United States, the incidence and prevalence of NENs have continued to rise over time, rendering their closest investigation imperative [2].…”
Section: Introductionmentioning
confidence: 99%